2017
DOI: 10.1371/journal.pone.0187110
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary angioedema: Assessing the hypothesis for underlying autonomic dysfunction

Abstract: BackgroundAttacks of Hereditary Angioedema due to C1-inhibitor deficiency (C1-INH-HAE)are often triggered by stressful events/hormonal changes.ObjectiveOur study evaluates the relationship between autonomic nervous system (ANS) and contact/complement system activation.MethodsTwenty-three HAE patients (6 males, mean age 47.5±11.4 years) during remission and 24 healthy controls (8 males, mean age 45.3±10.6 years) were studied. ECG, beat-by-beat blood pressure, respiratory activity were continuously recorded duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In recent years, several studies have suggested the interaction of the immune system with the central nervous system to explain the effects of mood and anxiety on inflammatory diseases [ 15 , 16 ]. A study in patients with C1-INH-HAE showing an increase in sympathetic activation at rest and a blunted response to experimentally induced stress have suggested that autonomous nervous system function may be altered [ 17 ]. Overall, studies addressing specifically the role of stress and psychological factors in C1-INH-HAE are still very limited, especially in children [ 10 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have suggested the interaction of the immune system with the central nervous system to explain the effects of mood and anxiety on inflammatory diseases [ 15 , 16 ]. A study in patients with C1-INH-HAE showing an increase in sympathetic activation at rest and a blunted response to experimentally induced stress have suggested that autonomous nervous system function may be altered [ 17 ]. Overall, studies addressing specifically the role of stress and psychological factors in C1-INH-HAE are still very limited, especially in children [ 10 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study has some limitations such as the small sample size. However, HAE is a rare disease, and groups of maximum 30 subjects were typically recruited in previous studies with similar design (Demirtürk et al, 2012 ; van Geffen et al, 2012 ; Wu et al, 2017 ). In addition, having studied HAE subjects only during inter-attack periods may have led to incomplete assessment of endothelial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with angioedema, at some predisposed locations, together with elevated BK level or decreased activity of ANG-1, mental stress may trigger angioedema attacks. Although noradrenaline was shown to be elevated in a tilt-induced stress model of C1-INH-HAE patients [ 23 ], the pathogenetic role of noradrenaline in increasing permeability is controversial [ 132 134 ]. Glucocorticoids are also increased during stress; however, their effects are questionable similarly to catecholamines, as glucocorticoids decrease permeability directly [ 197 ] as well as indirectly by reducing pro-inflammatory cytokine production of T cells and other leukocytes.…”
Section: Current Controversies In Bk-mediated Angioedemamentioning
confidence: 99%
“…BK-mediated angioedema involves a variety of plasma enzyme cascades (KKS, coagulation, fibrinolysis, and complement) [ 15 , 16 ], vascular endothelium [ 7 , 17 , 18 ], lymphatic endothelium [ 19 ], and cells of the immune system (e.g., neutrophil granulocytes) [ 20 ]. Various signaling pathways (such as ANGPT1-Tie2 signaling in HAE patients with ANGPT1 mutation) [ 21 ], hormonal effects [ 22 ], the autonomic nervous system [ 23 ], and other mechanisms yet to be discovered [ 24 ] may also contribute to the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%